The Protection of the Digital Medical file Between Privacy and Information Security - Fawzy Ahmed Awad, Amal (Journal of Legal Studies and Researches, 2021)
Health care practitioners throughout the world are keen to digitize and use health information technology solutions such as electronic health records to improve patient care quality, although technology has played a key role in the development of this area. But cyber-threats can cause complete paralysis and damage to medical systems, how will they address all legal and social challenges? the application of ongoing review policies to ensure the quality of the protection and privacy of information security has become necessary. The transition to digital is no longer a luxury, no choice, but a challenge today and a necessity for tomorrows and the currency of the future economy.